2021
DOI: 10.1371/journal.pone.0255096
|View full text |Cite
|
Sign up to set email alerts
|

Unified platform for genetic and serological detection of COVID-19 with single-molecule technology

Abstract: The COVID-19 pandemic raises the need for diverse diagnostic approaches to rapidly detect different stages of viral infection. The flexible and quantitative nature of single-molecule imaging technology renders it optimal for development of new diagnostic tools. Here we present a proof-of-concept for a single-molecule based, enzyme-free assay for detection of SARS-CoV-2. The unified platform we developed allows direct detection of the viral genetic material from patients’ samples, as well as their immune respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This enabled accurate classification of DMG patients according to H3 mutation status. While the classical enzyme-linked immunosorbent assay (ELISA) is frequently used for detection of protein biomarkers, it has low dynamic range and is highly limited to proteins present at high concentration in plasma 45,46 . Mass spectrometry-based methods for analysis of proteins in plasma are also biased towards more abundant proteins 47 .…”
Section: Discussionmentioning
confidence: 99%
“…This enabled accurate classification of DMG patients according to H3 mutation status. While the classical enzyme-linked immunosorbent assay (ELISA) is frequently used for detection of protein biomarkers, it has low dynamic range and is highly limited to proteins present at high concentration in plasma 45,46 . Mass spectrometry-based methods for analysis of proteins in plasma are also biased towards more abundant proteins 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Counting of single molecules confers high sensitivity 27,28 , thus we explored whether we could also quantify non-secreted tumor-specific plasma proteins that are undetectable by conventional technologies. We focused on the tumor suppressor p53, which is frequently mutated in CRC; p53 mutations lead to its stabilization and accumulation in tumor cells 29 .…”
mentioning
confidence: 99%
“…In addition to the unique epigenetic analysis, the single-molecule system outperforms the classical ELISA assay for measuring protein biomarkers. ELISA is of relatively low sensitivity and is therefore limited to proteins that are present at high levels, has lower dynamic range in quantifying proteins, and is not amenable to multiplexed detection of several proteins 27,28 . We showed that the single-molecule system is capable of detecting the mutant form of p53, which is a non-secreted protein that originates directly from the tumor cells.…”
mentioning
confidence: 99%